A comparative study on young-adult decision-making behaviour in regions within Malaysia. (1st January 2012) - Keoy, Kay Hooi; Yee, Audrey Sin Lye; Hassan, Padzil
Consumers constantly required making decision regarding choices, purchases and use of products and services. This decision is often difficult as various expect needs to be evaluated during the decision-making process to obtain a desirable outcome. Further to this, there is also evidence that shows the high failure rate of businesses was attributed to consumer. In the present study, the purpose is to evaluate the extent of young-adult consumers' decision-making behaviour between the two chosen regions that varies, which impact on consumers' buying behaviour. The required information was collected from 100 respondents who were randomly selected from two regions in Malaysia. The findings revealed that there are no statistical significant differences in these young-adult consumers' buying behaviour between two regions in Malaysia.